A survey across orbital lymphoma in Poland: Multicenter retrospective study of polish lymphoma research group (PLRG). (26th September 2022) - Kalicińska, Elżbieta; Giza, Agnieszka; Zaucha, Jan Maciej; Giebel, Sebastian; Zimowska‐Curyło, Dagmara; Andrasiak, Iga; Spychałowicz, Wojciech; Wojnar, Jerzy; Balcerzak, Andrzej; Romejko‐Jarosińska, Joanna; Paszkiewicz‐Kozik, Ewa; Knopińska‐Posłuszny, Wanda; et al.
Abstract: Objective: To investigate the prevalence of histopathological subtypes, the clinical stage at presentation and treatment modalities in Polish patients with orbital lymphoma (OL) and to determine prognostic outcomes. Methods: The retrospective study of 107 patients with OL treated in a 14‐year period in Polish hematological centers. The analysis included histopathological subtype, disease clinical advancement, treatment modalities, progression‐free survival (PFS), and overall survival (OS). Results: The median patient age was 60 years (range 51–71). Mucosa‐associated lymphoid tissue (MALT) lymphoma accounted for slightly more than half of all cases of orbital lymphoma (51%). The second most common subtype was diffuse large B‐cell lymphoma (DLBCL) (29%). Primary orbital lymphoma was diagnosed in 48% of all patients. According to the Ann Arbor, localized stage IE of orbital lymphoma was diagnosed only in 39% of all patients. Systemic involvement was observed in more than half of all patients (52%). The median follow‐up period was 30 months (range 0–160 months). Patients with non‐MALT lymphoma had a significantly inferior PFS compared to patients with MALT lymphoma, ( p  = 0.047). Patients with primary orbital lymphoma had a superior PFS compared to patients with secondary orbital lymphoma [median PFS 104.5 months vs. 33.4 months], ( p  = 0.069). Younger patients with MALT lymphoma were characterized by superior PFS (median PFS not reached) compared to other studied subgroups of patients (older patients with MALT lymphoma, younger and older non‐MALT lymphoma patients) with a median PFS of 30.5, 32.2, 32.6 months respectively ( p  = 0.039). Patients treated with chemotherapy alone had inferior PFS compared to patients treated with combined therapies ( p  = 0.034). The median PFS across patients who received chemotherapy alone was 23.7 months, whereas across other patients was 73.9 months. Conclusions: Secondary lymphoma accounts for more than half of the orbital lymphoma in Polish population. The advanced clinical stage of the disease (non‐IE according to Ann Arbor) concerns two‐thirds of the overall population of patients with orbital lymphomas and one‐third of MALT lymphoma patients. The high incidence of advanced stages of orbital lymphoma may indicate the need for combined treatment. Combined orbital lymphoma treatment is associated with superior PFS compared to chemotherapy alone in overall population of patients with orbital lymphoma. Abstract : The advanced clinical stage of the disease (non‐IE according to the Ann Arbor) concerns two thirds of the overall population of patients with ocular adnexal lymphoma and one third of MALT lymphoma patients. Due to the high prevalence of advanced stages of ocular adnexal lymphoma, treatment with combined therapies is warranted. Combined treatment tends to improve PFS compared to chemotherapy alone in the overall population of patients with ocular adnexal lymphoma.